Sealing Performance Analysis of Lip Seal Ring for High-Speed Micro Bearing - Hengdi Wang; Yulu Yue; Yongcun Cui; Xiaobiao Qiu; Chang Li (Lubricants)
This article focuses on the problem of sealing failure in high-speed micro bearings. Based on a thermal-stress coupled finite element model, the distribution of equivalent stress and contact pressure of the sealing ring and the influence of various factors on the sealing performance are analyzed. Based on this, the Latin Hypercube sampling method, Kriging surrogate model and genetic algorithm are used to find the optimal combination of sealing performance. Finally, the accuracy of the model and method is verified through orthogonal experiments. Research has found that the maximum equivalent stress of the seal ring is 0.59234 MPa, and it increases first and then decreases with the increase in lip inclination angle, friction coefficient and radial interference amount, increases with the increase in lubricant temperature, and decreases with the increase in bearing rotation speed. The maximum contact pressure is 0.20433 MPa, and it decreases with the increase in the lip inclination angle, increases first and then decreases with the increase in the friction coefficient, and decreases first and then increases with the increase in the lubricant temperature, bearing rotation speed and radial interference amount. The most significant factor affecting the equivalent stress of the seal ring is the lubricant temperature, and the most significant factor affecting the contact stress is the interference fit amount. When the seal lip inclination angle is 43.99°, the friction coefficient is 0.01 mm, the lubricant temperature is 111.5 °C, the bearing rotation speed is 28,853 rpm and the radial interference amount is 0.04 mm, the sealing performance of the sealing ring is optimal.